Climatology of cyclones in western and northwestern Iran using reanalysis and remote sensing data. (6th July 2022) - Ghasemifar, Elham; Hardy, Sam; Minaei, Masoud
Abstract: Agriculture and hydrological management in western and northwestern Iran is highly sensitive to precipitation associated with Mediterranean and Sudanese cyclones particularly during spring and winter. Although many studies have focused on the theoretical basis of these cyclones, statistical analyses, especially with satellite observations, have not been undertaken. In this study, 40 cyclones during all months of 2015–2021 are characterized using data collected by Global Precipitation Measurement (GPM) dual‐frequency precipitation radar (DPR), Tropical Rainfall Measuring Mission (TRMM) Multisatellite Precipitation Analysis (TMPA) and ERA5 reanalysis within each cyclone quadrant. The results show that about 45% of cyclones have a lifetime between 1 and 2 days, and approximately 25% occur during April with a secondary peak in March (22.5%). Accordingly, cyclonic rainy days and rainfall amounts peak in April with values of 76.1% and 64.1%, respectively. The lowest (most negative) low‐ and mid‐tropospheric vertical velocity in the southeast and northeast quadrants indicates upward motion, which leads to the most intense latent heat release within the cyclone. Accordingly, the highest rainfall rates occur in the southeast and northeast quadrants, located within and ahead of the highest specific humidity quadrant (southeast) where the warm conveyor belt plays a significant role for rainfall formation. Maximum stratiform and convective rainfall rates are observed in the southwest and southeast quadrants, respectively. The distribution of rainfall rate is consistent with that of the storm‐top height pattern in all quadrants. The maximum percentage of warm rain to the total rain (34.6% on average) for both stratiform and convective precipitation falls in the southeast quadrant. The structure of these analysed cyclones is largely similar to that shown previously in the literature. According to the analysed rainfall in different life cycles, it is expected that the cyclones have the greatest impact (i.e., extreme rainfall) during the developing stage in the northeast and southeast quadrants, and during the mature stage in the southwest quadrant. The lowest influence is during the dissipating stage. The results from this study can help decision makers within the hydrological and risk management industries. Abstract : (a) Identifiying the cyclones impacting west and northwest Iran during all months of the period 2015–2021. (b) Quantifiying the identified cyclones using weather stations data. (c) Compositie analysing of these cyclones using ERA5 large‐scale parameters and GPM DPR data. (d) The azimuthal relationship between GPM DPR rainfall and storm‐top height.